A study of wound healing process in post total laryngectomy patients: Serial case reports - Srifia Wardianti; Iskandar Zulkarnain; Benny Kurnia; Lily Setiani; Fadhlia Fadhlia; Safarianti Safarianti (Trends in Infection and Global Health, 2022)
Laryngeal carcinoma is a malignancy on larynx that may occur in glottic, supraglottic and subglottic. Larynx plays role in coordination of upper aerodigestive tract such as breathing, verbal and swallowing. This reported as the third most common malignancy in the ENT-HN department. Total laryngectomy is a procedure that performed on T3 and T4 lesions. The most common complication is prolonged of the wound healing process. The process is very complex  consist of four overlapping phases that involve multifactorial divided into local and systemic factors. Local factors include oxygenation and infection, while systemic factors are age, gender, psychological stress, nutrition, chronic disease and immunocompromise conditions. In this case, seven patients underwent total laryngectomy and contributing factors of wound healing process were observed in each patient until 14th postoperative day. Some of important factors might contributed to the wound healing process in some patients such as psychological stress, nutrition and chronic disease such as diabetes mellitus and hypertension.